Acolhimento psicossocial no contexto da atenção à saúde de servidores públicos federais - Rebello, Mariana de Oliveira (2020)
The health care of the federal public servant was structured with the creation of the Integrated Subsystem of Health Care of the Federal Public Servant (SIASS), in 2009, and the Policy of Attention to Health and Safety at Work of the Federal Public Servant (PASS), from 2013. SIASS coordinates actions and programs in the areas of health care, official expertise, health promotion, prevention and monitoring of civil servants of the direct, autarchic and foundational federal administration. In this context, the present study aimed to understand the way in which federal civil servants attended in the Psychosocial Reception Service of the SIASS Reference Unit relate dimensions of the organization of work in the institution with their psychological suffering and the contributions of welcoming to their health. This is a descriptive and exploratory study, of a qualitative nature, developed with documentary research and interviews with a semi-structured script. The study scenario was a SIASS Unit linked to the federal educational institution in the Southeast Region of Brazil. Theoretical saturation sampling guided the construction of data. Participants were thirteen servers served at SAP in 2019, who worked at a federal educational institution under the statutory regime as a teacher or administrative technician in education. Thematic content analysis guided data analysis. Three categories were built: Occupational health at a federal institution; Psychosocial Reception Service according to users; Psychic suffering. The theoretical-analytical framework was the Psychodynamics of Work. Among the participants, six referred to work-related mental illness issues; six sought guidance related to mental disorders and one presented illness due to grief. The servers consider the SAP as a reference for welcoming in times of crisis, a care device that has led to reflections about themselves and their work relationships. The continuity of care in other actions and programs of the SIASS unit was pointed out as a limitation. Different perceptions of work were exposed by the employees: attribution of meaning to existence, source of support, financial independence, bonding, displeasure and suffering. The organization of work, overload, lack of recognition and focus on productivity are sources of displeasure and psychological suffering by employees. Productivism and hierarchical relationships between employees and managers were described as influences of the market logic in the public institution. Due to the close relationship between work organization and the psychological suffering of civil servants, there is an urgent need to discuss the management model adopted by the Brazilian State that permeates the daily life of federal educational institutions. The study indicates the high demand for mental health by the civil servants and the importance of expanding the services offered by SIASS.